Service Quality, Brand Image, and Electronic Word of Mouth as Key Drivers of Consumer Loyalty in E-Commerce: A Study of Shopee Users in Indonesia - Fendha Theodany; Astri Ayu Purwati; Sarbaeni Sarbaeni (Yayasan Pendidikan Islam Al-Matani, 2025)
This study aims to examine the influence of service quality, brand image, and electronic word of mouth (eWOM) on customer loyalty toward Shopee e-commerce in Pekanbaru City, Indonesia. The study population consists of Shopee users in Pekanbaru City, for which the exact population size is unknown. A non-probability sampling approach was employed using an accidental sampling technique. Based on Roscoe’s rule of thumb, a total of 150 respondents were selected as the research sample. Data were collected through a structured questionnaire and analyzed using the Statistical Package for Social Sciences (SPSS). The results reveal that service quality, brand image, and electronic word of mouth (eWOM) each have a significant and positive effect on customer loyalty. These findings indicate that improving service performance, strengthening brand perception, and encouraging positive online customer reviews are critical strategies for enhancing customer loyalty in the highly competitive e-commerce sector. This study contributes to the literature on digital marketing and consumer behavior by providing empirical evidence from an emerging market context.